Ex Vivo Visualization of Distribution of Intravitreal Injections in the Porcine Vitreous and Hydrogels Simulating the Vitreous - Tobias Auel; Lara Paula Scherke; Stefan Hadlich; Susan Mouchantat; Michael Grimm; Werner Weitschies; Anne Seidlitz (MDPI AG, 2023)
The characterization of intravitreal dosage forms with regard to their behavior in vivo is usually explored in preclinical development through animal studies. In vitro vitreous substitutes (VS) to simulate the vitreous body for preclinical investigations have so far been insufficiently studied. To determine a distribution or concentration in the mostly gel-like VS, extraction of the gels is required in many cases. This destroys the gels, which makes a continuous investigation of the distribution impossible. In this work, the distribution of a contrast agent in hyaluronic acid agar gels and polyacrylamide gels was studied by magnetic resonance imaging and compared with the distribution in ex vivo porcine vitreous. The porcine vitreous served as a surrogate for human vitreous since both are similar in their physicochemical properties. It was shown that both gels do not completely represent the porcine vitreous body, but the distribution in the polyacrylamide gel is similar to that in the porcine vitreous body. In contrast, the distribution throughout the hyaluronic acid agar gel is much faster. It was also shown that anatomical features such as the lens and the interfacial tension to the anterior eye chamber could have an influence on the distribution that is difficult to reproduce using in vitro VS. However, with the presented method, new in vitro VS can be investigated continuously without destruction in the future, and thus their suitability as a substitute for the human vitreous can be verified.